2021
DOI: 10.7554/elife.68544
|View full text |Cite
|
Sign up to set email alerts
|

The molecular appearance of native TRPM7 channel complexes identified by high-resolution proteomics

Abstract: The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed membrane protein consisting of ion channel and protein kinase domains. TRPM7 plays a fundamental role in the cellular uptake of divalent cations such as Zn2+, Mg2+, and Ca2+, and thus shapes cellular excitability, plasticity, and metabolic activity. The molecular appearance and operation of TRPM7 channels in native tissues have remained unresolved. Here, we investigated the subunit composition of endogenous TRPM7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 74 publications
(93 reference statements)
4
40
0
Order By: Relevance
“…Overexpression of ARL15 in renal carcinoma cells decreased cellular Mg2+ uptake, whereas KO of the protein increased it [33]. While our manuscript was under review, a preprint appeared on the bioRxiv server, reporting that macromolecular complexes of TRPM7, CNNMs, PRLs, and ARL15 can be detected in rodent brain [63]. The article, which was recently accepted for publication, demonstrated that heterologous overexpression of ARL15 with TRPM7 in HEK-293 cells suppressed TRPM7 channel activity [64].…”
Section: Plos Biologymentioning
confidence: 93%
See 2 more Smart Citations
“…Overexpression of ARL15 in renal carcinoma cells decreased cellular Mg2+ uptake, whereas KO of the protein increased it [33]. While our manuscript was under review, a preprint appeared on the bioRxiv server, reporting that macromolecular complexes of TRPM7, CNNMs, PRLs, and ARL15 can be detected in rodent brain [63]. The article, which was recently accepted for publication, demonstrated that heterologous overexpression of ARL15 with TRPM7 in HEK-293 cells suppressed TRPM7 channel activity [64].…”
Section: Plos Biologymentioning
confidence: 93%
“…While our manuscript was under review, a preprint appeared on the bioRxiv server, reporting that macromolecular complexes of TRPM7, CNNMs, PRLs, and ARL15 can be detected in rodent brain [63]. The article, which was recently accepted for publication, demonstrated that heterologous overexpression of ARL15 with TRPM7 in HEK-293 cells suppressed TRPM7 channel activity [64]. Using the Zn 2+ influx assay, we similarly found that overexpression of ARL15 inhibited TRPM7-mediated Zn 2+ influx (S12 Fig) . Conversely, we also find that knockdown of ARL15 in HEK-293 cells increased TRPM7-mediated Zn 2+ influx (S12 Fig) . Thus, PRLs and ARL15 appear to have opposing actions on TRPM7 function.…”
Section: Plos Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that CNNM proteins can interact with the Mg 2+ channel transient receptor potential receptor type 7 (TRPM7) in vivo and vitro. [ 117 ] ARL15 reduced TRPM7-mediated currents in X. laevis oocytes upon heterologous overexpression, suggesting a potential, complex regulatory mechanism of ARL15-CNNM regulation on TRPM7 channel activity.…”
Section: Main Bodymentioning
confidence: 99%
“…There are many unanswered questions about the biological function of PRLs but also signs that the gaps in our understanding are closing. One promising development is the realization that CNNM proteins are associated with another family of proteins, the melastatin-related transient receptor potential ion channels, TRPM6 and TRPM7 ( 61 , 84 , 85 , 86 , 87 ). Like CNNMs, TRPM6/7 are important for magnesium homeostasis and have been implicated in cancer ( 55 , 88 , 89 , 90 ).…”
Section: Perspectives and Conclusionmentioning
confidence: 99%